A Narrative Review on the In Vivo Evaluation of Iron Bioavailability to Assess the Effectiveness of Food Fortification and Biofortification: Narrative Review on the In Vivo Evaluation of Iron Bioavailability in Food Fortification - Haneen Basori; Malvin Widyanto Tjoa; Felycia Angellia; Gracia Angelina Wan; Rike Tri Kumala Dewi; Dwining Putri Elfriede (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2026)
Iron deficiency anemia remains a major global health problem, with a prevalence reaching 40% among children aged 6–59 months, 37% among pregnant women, and 30% among women of reproductive age. Low iron bioavailability is a key limiting factor affecting the effectiveness of nutritional interventions. This review aimed to analyze various in vivo methods used to evaluate iron bioavailability from food sources and to assess the effectiveness of fortification, biofortification, and food processing modifications. A narrative review approach was conducted through literature searches in Google Scholar, ScienceDirect, Wiley, MDPI, and Garuda databases for original research articles published between January 2016 and March 2026, with March 2026 as the search cutoff to ensure inclusion of fully indexed publications only. Of the 24 identified articles, 8 met the inclusion criteria and were analyzed descriptively. The findings indicate that in vivo studies employed various parameters, including hemoglobin regeneration efficiency, relative biological value, fractional iron absorption, hemoglobin concentration, serum ferritin, and organ iron retention. Notably, iron bioavailability was not always proportional to total iron content in food, as biofortification and fermentation strategies improved physiological iron utilization primarily by reducing inhibitory compounds such as phytate, rather than by increasing total iron content. Food matrix, chemical form of iron, and physiological status of subjects were identified as the most critical determinants of iron absorption effectiveness.